Production of strawberry using internet of things: a review - Olakunle Elijah; Abdelmoneim A. bakhit; Tharek A. Rahman; Tien Han Chua; Siti Fatimah Ausordin; Rifhan Narrissa Razali (Institute of Advanced Engineering and Science, 2019)
Strawberry is a widely consumed fruit and cultivated globally but predominantly in cooler temperate zones because of its wealth of nutrients, vitamins and minerals. However, there are several challenging factors faced in the growing of strawberry such as temperature, seasonal production and short shelf-life. To overcome some of these challenges, the application of greenhouse and internet of things (IoT) are being used. In this paper, a review of the application of IoT in the greenhouse production of strawberry is presented. This includes a survey of existing literature on production of strawberry, types, method of growing strawberry and the application of IoT. The benefits and challenges of IoT in greenhouse strawberry production are discussed. The review highlights the need for use of low power wide area communication technology in the application of IoT in greenhouse strawberry production especially in tropical regions like Malaysia.